Increasing skill reading intensive and character of classes III SDN 57 air dingin using cooperative learning model circ - Elizawati Elizawati; Syahrul Syahrul; Yalvema Miaz (Jurnal Aplikasi IPTEK Indonesia, 2018)
Based on the observations in class III SDN Air Dingin, found the intensive reading skill of third grade students low. For that, it needs improvement to help students in reading intensively with the correct reading stage. This study aims to describe the process and the results of intensive reading skills and character of third grade students. The type of research is Classroom Action Research using cooperative learning model of CIRC type. Based on the results of the research, the use of cooperative learning model of CIRC type in intensive reading skill learning has proven to improve the process of intensive reading skill and student character. The increase in the average learning outcomes is, in the first cycle at the pre reading stage of 71.87%, the stage when reading 59.37%, 76.37% post reading stage and characteristic scoring 69.75%, confident 60.95% and well mannered 71.17%. In the second cycle, the students' intensive reading skill increased to 84.37% pre reading, reading 78.12% and post reading 83.12% and characteristic meticulous assessment 74.27%, 78.32% confident and 76.25% polite. Intensive reading using the CIRC approach has been shown to improve students' reading and character skills.